From laboratory to market: the contribution of academic innovation to local economic development - Kamarullah, Shahida Hanum; Zainuddin, Nur Sha’adah; Ab Manan, Wan Noni Afida (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Universities are increasingly expected to drive regional economic transformation through innovation, extending beyond their traditional roles of teaching and research. In today’s knowledge-driven economy, the “lab-to-market” model highlights how academic research can be translated into real economic and societal value. This transformation involves collaboration among faculty as research leaders, students as emerging entrepreneurs, and local communities as co-creators and beneficiaries. Through startups, commercialization, and partnerships with stakeholders, universities help develop solutions to regional challenges while strengthening economic resilience and ensuring that the benefits of innovation reach wider society (Etzkowitz et al., 2020).